Whole-genome sequencing provides insights into the genetic diversity and domestication of bitter gourd (Momordica spp.). (1st June 2020) - Cui, Junjie; Yang, Yan; Luo, Shaobo; Wang, Le; Huang, Rukui; Wen, Qingfang; Han, Xiaoxia; Miao, Nansheng; Cheng, Jiaowen; Liu, Ziji; Zhang, Changyuan; Feng, Chengcheng; et al.
Abstract: Bitter gourd ( Momordica charantia ) is a popular cultivated vegetable in Asian and African countries. To reveal the characteristics of the genomic structure, evolutionary trajectory, and genetic basis underlying the domestication of bitter gourd, we performed whole-genome sequencing of the cultivar Dali-11 and the wild small-fruited line TR and resequencing of 187 bitter gourd germplasms from 16 countries. The major gene clusters ( Bi clusters) for the biosynthesis of cucurbitane triterpenoids, which confer a bitter taste, are highly conserved in cucumber, melon, and watermelon. Comparative analysis among cucurbit genomes revealed that the Bi cluster involved in cucurbitane triterpenoid biosynthesis is absent in bitter gourd. Phylogenetic analysis revealed that the TR group, including 21 bitter gourd germplasms, may belong to a new species or subspecies independent from M. charantia . Furthermore, we found that the remaining 166 M. charantia germplasms are geographically differentiated, and we identified 710, 412, and 290 candidate domestication genes in the South Asia, Southeast Asia, and China populations, respectively. This study provides new insights into bitter gourd genetic diversity and domestication and will facilitate the future genomics-enabled improvement of bitter gourd.